Room-Temperature Magnetic Switching of the Electric Polarization in Ferroelectric Nanopillars - Poddar, Shashi; de Sa, Pedro; Cai, Ronggang; Delannay, Laurent; Nysten, Bernard; Piraux, Luc; Jonas, Alain M (ACS nano, 2018)
Magnetoelectric layers with a strong coupling between ferroelectricity and ferromagnetism offer attractive opportunities for the design of new device architectures such as dual-channel memory and multiresponsive sensors and actuators. However, materials in which a magnetic field can switch an electric polarization are extremely rare, work most often only at very low temperatures, and/or comprise complex materials difficult to integrate. Here, we show that magnetostriction and flexoelectricity can be harnessed to strongly couple electric polarization and magnetism in a regularly nanopatterned magnetic metal/ferroelectric polymer layer, to the point that full reversal of the electric polarization can occur at room temperature by the sole application of a magnetic field. Experiments supported by finite element simulations demonstrate that magnetostriction produces large strain gradients at the base of the ferroelectric nanopillars in the magnetoelectric hybrid layer, translating by flexoelectricity into equivalent electric fields larger than the coercive field of the ferroelectric polymer. Our study shows that flexoelectricity can be advantageously used to create a very strong magnetoelectric coupling in a nanopatterned hybrid layer.